Martin Schreiner and Jewish Theology: An Introduction - Turán, Tamás (European Journal of Jewish Studies, 2017)
Martin Schreiner (1863-1926), a rabbi in Hungary and later a professor at the liberal rabbinical seminary in Berlin, was a disciple of David Kaufmann and Ignaz Goldziher, and a prominent scholar of Medieval Islamic and Jewish thought. The present article deals with his little-known contributions to religious thought in the late nineteenth century, utilizing also his unpublished work on Jewish religious philosophy and his correspondence with Goldziher. Schreiner's unique quest for a combination of liberal, academic Jewish theological inquiry with conservative loyalty to religious law-a precarious stance, a neo-Maimonidean attitude of sorts-confronted and challenged all the religious platforms which evolved in modern Judaism.